Early clinical experiences with nintedanib in three UK tertiary interstitial lung disease centres. Issue 1 (3rd November 2017) - Toellner, Hannah; Hughes, G.; Beswick, W.; Crooks, M. G.; Donaldson, C.; Forrest, I.; Hart, S. P.; Leonard, C.; Major, M.; Simpson, A. J.; Chaudhuri, N.
Abstract: Background: Nintedanib has been shown to slow disease progression in patients with idiopathic pulmonary fibrosis (IPF). It was approved by the National Institute for Health and Care Excellence (NICE) in January 2016 for IPF patients with a forced vital capacity (FVC) of 50–80% in the United Kingdom (UK). Aim: To report real world data about our early clinical experience using nintedanib in 187 patients with a multi‐disciplinary (MDT) diagnosis of IPF in a manufacturer funded patient in need scheme (three UK centres) prior to NICE approval. Methods: All patients with a MDT diagnosis of IPF from December 2014 to January 2016 commenced on nintedanib were included. Demographic details, adverse events (AEs) and where available lung function results were retrospectively collected from clinical letters. Results: 187 patients (76% males) with a median age of 72 years (49–89) were treated with nintedanib. The average pre‐treatment FVC was 81.1 ± 19.8% and diffusion capacity of the lungs for carbon monoxide was 43.9 ± 15% (n = 82). Fifty percent of patients started nintedanib because they were ineligible for pirfenidone due to an FVC > 80%. The median treatment course was 8 ± 4 months. The majority of patients experienced 1–3 AEs with nintedanib (52%, n = 97). The most frequent AEs were diarrhoea (50%), nausea (36%), reduced appetite (24%), tiredness (20%) and gastro‐oesophageal reflux (18%). The majority of AEs resulted in no change in treatment (64%, n = 461). 21% (n = 150) of AEs resulted in a dose reduction and 13% (n = 94) necessitated discontinuation of treatment. 1 in 5 patients discontinued treatment either temporarily or on a permanent basis during the monitoring period. In a select cohort of patients, a statistically significant greater proportion of patients remained stable or improved and a lower proportion declined, as depicted by FVC changes of > 5% after nintedanib commencement (P < 0.05 using Chi squared test). Conclusions: Nintedanib is well tolerated and has an acceptable safety profile. Only 8% of those reporting diarrhoea discontinued treatment either on a temporary or permanent basis. There were no signals with respect to increased cardiovascular morbidity or major bleeding risk. This is in keeping with the INPULSIS clinical trial findings but in a real world cohort.